2013
DOI: 10.3109/14767058.2013.825598
|View full text |Cite
|
Sign up to set email alerts
|

Occiput posterior position diagnosis: vaginal examination or intrapartum sonography? A clinical review

Abstract: The occiput posterior (OP) position is one of the most frequent malposition during labor. During the first stage of labor, the fetal head may stay in the OP position in 30% of the cases, but of these only 5-7% remains as such at time of delivery. The diagnosis of OP position in the second stage of labor is made difficult by the presence of the caput succedaneum or scalp hair, both of which may give some problem in the identification of fetal head sutures and fontanels and their location in relationship to mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 25 publications
2
32
1
4
Order By: Relevance
“…Our rate of VM in labor (5.3%) is lower than that of 10-30% reported elsewhere [3][4][5] , but that of persistent Occipito-Posterior (OP) position (89.2%) is higher than the rates of 1.8% to 10.8% found by others. 1,6,15 Because of low spontaneous rotation rate, our rate of persistent OP position at delivery (3.0%) is within the range of 1.8% to 6.0% found elsewhere.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Our rate of VM in labor (5.3%) is lower than that of 10-30% reported elsewhere [3][4][5] , but that of persistent Occipito-Posterior (OP) position (89.2%) is higher than the rates of 1.8% to 10.8% found by others. 1,6,15 Because of low spontaneous rotation rate, our rate of persistent OP position at delivery (3.0%) is within the range of 1.8% to 6.0% found elsewhere.…”
Section: Discussioncontrasting
confidence: 81%
“…[3][4][5] Risk factors for VM include nulliparity, maternal obesity, excessive fetal weight, pelvic (especially mid cavity) immaturity or abnormalities, epidural anesthesia and labor augmentation. 2,6,7 Diagnosis of OP position is done through a digital vaginal examination which finds the lambda fontanel towards the maternal sacrum.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In most of these cases the option of proceeding to Cesarean delivery is considered despite failing to achieve a precise diagnosis of the underlying cause of dystocia. On the other hand, as previously reported also by our group for anterior asynclitism or face presentation, the use of ultrasound may assist the clinician in the exact diagnosis and the visual documentation of a malposition.…”
Section: Discussionsupporting
confidence: 59%
“…Over the past decades, several studies have demonstrated that clinical diagnosis of fetal head position by means of digital examination is highly inaccurate, particularly in cases of occiput posterior or occiput transverse position. On the other hand, evaluation of the fetal head position using transabdominal sonography (TAS), either during labor or before instrumental delivery, has proven to be far more accurate.…”
Section: Introductionmentioning
confidence: 99%